2020
DOI: 10.3390/nano10122390
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Homogeneous Luminescent Silicon–Terbium Nanowires by One-Step Electrodeposition in Ionic Liquids

Abstract: An electrodeposition method for the growth of homogeneous silicon–terbium nanowires (NWs) with green light emission is described. The method involves template-assisted electrochemical co-deposition of Si/Tb NWs with 90-nm diameter from an electrolyte bath containing Si and Tb precursors in an ionic liquid (IL). This method of deposition is advantageous over other conventional techniques as it is relatively simple and cost-effective and avoids harsh deposition conditions. The deposited NWs are of uniform dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Lanthanide (Ln) elements have been studied extensively in diverse industrial applications of magnets, high-k gate dielectrics, display materials, catalysts, and batteries [1][2][3][4][5][6]. For recycling used Ln materials, various recovery methods for Ln elements have also been demonstrated [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanthanide (Ln) elements have been studied extensively in diverse industrial applications of magnets, high-k gate dielectrics, display materials, catalysts, and batteries [1][2][3][4][5][6]. For recycling used Ln materials, various recovery methods for Ln elements have also been demonstrated [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the electrochemical redox behaviors of Ln ions have been studied extensively for the development of reprocessing technology (e.g., pyroprocessing technology) of used nuclear fuels [14,15]. For their studies of electrochemical behaviors and electrodeposition, Thomas et al successfully demonstrated that silicon-terbium nanowires could be prepared using a one-step electrodeposition method in an electrolyte containing an ionic liquid of 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 10 mM SiCl 4 , and 10 mM TbCl 3 [2]. Song et al demonstrated Ni-P-ZrO 2 -CeO 2 composite coatings on #45 steel using the jet-electrodeposition technique and achieved an optimal coating condition (e.g., potential and current density) for improving surface properties, hardness, and wear resistance [16].…”
Section: Introductionmentioning
confidence: 99%
“…The role of IL was used to extract the LnPO 4 into the organic phase from the aqueous phase via capping it (Zhang and Chen, 2019 (He et al, 2011a;He et al, 2011b;He et al, 2012;Pan et al, 2013). The onestep electrodeposition in IL (1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide [Py 1,4 ][TFSI]) method is employed for synthesizing the luminescent silicon-terbium nanowires by Thomas et al (2020). Another group has prepared the luminescent LaPO 4 :Ce,Tb phosphors using ILdriven liquid membrane system.…”
Section: Preparative Methods For Lanthanide Ion(s)-doped Nanomaterials Using Ilmentioning
confidence: 99%
“…Annealing can crystallize silicon deposits without changing their shape and structure. Such a strategy may replace the more restrictive high-vacuum approach, and the synthesized homogeneous silicon nanomaterials have promising applications in microelectronics and optoelectronics [ 145 , 146 ].…”
Section: State-of-the-art Silicon Electrochemical Extraction Strategi...mentioning
confidence: 99%